Economic Geology Models 1. Geochemical Exploration and Metallogenic Studies, Northern Chile - Cameron, Eion M.; Leybourne, Matthew I.; Palacios, Carlos; Reich, Martin (Geoscience Canada, 2008)
Research was initiated in 1998 on geo-chemical methods of exploration for copper porphyry deposits buried under thick, lithified piedmont gravel cover in the Atacama Desert, Chile. Early data suggest that mineralized, saline groundwater has been episodically forced up through fracture zones to the surface during earthquakes, creating geochemical anomalies above ore deposits. Follow-up research supported by the Canadian Mining Industry Research Organization (CAMIRO) examined the composition of both groundwater and surface anomalies, confirming a link between the two. Further work suggests that the geo-chemical anomalies are the surface expression of a process common to the metallogenic evolution of many deposits. Porphyry intrusion and hypo-gene mineralization are controlled by faults, and are followed by supergene enrichment in a semi-arid climate. After burial by Miocene gravels, the climate changed to hyper-arid; estimates of the onset of hyperaridity vary from mid-Miocene (11–14 Ma) to Pliocene ( 3–5 Ma). Since then, saline dewatering of the basement along long-lived faults has converted the original super-gene copper oxide assemblage, formed in equilibrium with meteoric water and lacking atacamite, to one containing atacamite [Cu2Cl(OH)3], the copper mineral especially associated with northern Chile. This interpretation is supported by studies showing that the salinity of fluid inclusions in atacamite is similar to that of local groundwater and that atacamite is considerably younger than the co-existing supergene alteration. SOMMAIRE La recherche décrite ici et initiée en 1998 visait à mettre au point des méth-odes d’exploration de gisements de porphyres cuprifères enfouis sous d’épaisses couches lithifiées de graviers dans le désert d’Atacama au Chili. Des données préliminaires indiquent que des eaux souterraines salines minéralisées ont été poussées épisodiquement jusqu’à la surface, à travers des zones de fractures, à l’occasion de séismes, créant ainsi des anomalies au-dessus de gisements minéraux. Une recherche subséquente appuyée par la Canadian Mining Industry Research Organization (CAMIRO) qui a porté sur la composition de l’eau souterraine et des anomalies de surface, a permis de confirmer l’existence d’un lien entre les deux. Les résultats de travaux subséquents permettent de croire que ces anomalies géochimiques sont l’expression en surface d’un processus commun à l’évolution métallogénique de nombreux gisements. L’intrusion porphyrique et la minéralisation hypogène sont tributaires de failles, auxquelles s’est ensuite ajouté un enrichissement supergène sous climat semi-aride. Après l’enfouissement au Miocène par des graviers, le climat est devenu hyper-aride; selon les estimations le climat serait devenu hyperaride entre le Miocène moyen (11-14 Ma) et le Pliocène ( 3-5 Ma). Depuis, l’assèchement des eaux salines du socle le long de failles persistantes a entraîné une conversion de l’assemblage original d’oxydes de cuivre supergène - lequel s’était formé en état d’équilibre en milieu d’eau météorique et qui était dépourvu d’atacamite - en un assemblage contenant de l’atacamite [Cu2Cl(OH)3], ce minéral de cuivre typique du Chili du nord. Cette interprétation est corroboré par des études montrant que la salinité des inclusions fluides dans l’atacamite est semblable à celle de l’eau souterraine locale et que l’atacamite est significativement plus jeune que l’altération supergène coexistante.